Alberta's Data Mobilization Strategy: Leveraging Linked Data for Innovation - Svenson, Larry; Simmonds, Kimberley; Perry, Alexa; Riemer, Justin (International Journal of Population Data Science, 2018)
Introduction The Province of Alberta maintains a mature data ecosystem with linkable data dating back over 30 years. The population-based nature of the data makes this a valuable asset for driving analytics to support health system innovation, with a focus on improving health outcomes and quality of life. Objectives and Approach Alberta Health has created the Secondary Use Data Access (SUDA) initiative to leverage its administrative health data. SUDA envisions strengthening partnerships between the public and private sectors with two main access approaches. The first is direct access to de-identified data held within the Alberta Health data warehouse by key health system stakeholders (e.g. academic instituions, Health Quality Council of Alberta, regulatory colleges). The second is indirect access to private and not-for-profit stakeholders, using a safe haven approach. Indirect access is achieved through private sector investments to a trusted third party that hires analysts to be placed within Alberta Health. Results Staffing agreements and privacy impact assessments have been drafted to support the work. The indirect access route includes a multiple stakeholder steering committee to vette and prioritize projects. Private and not-for-profit stakeholders do not have access to the data, but rather receive access to aggregate data and statitstical models. All disclosures are done by Alberta Health staff to ensure compliance with Alberta's Health Information Act. Direct access has been established for the Alberta Medical Association as part of a long standing data sharing agreement, with access restricted to de-identified data only. To date, seven industry proposals for analytics have been received and are currently being actioned. Conclusion/Implications The Secondary Use Data Access initiative uses a safe haven approach to leveraging data. It reduces the need to provision data outside of the data warehouse and allows for better monitoring of access and use of data. The approach provides assurances that people's health information is secure.